Documentation as Art Practice in the 1960s. (1st October 2016) - Berger, Christian; Santone, Jessica
Abstract : This issue addresses the practice of documentation in the art of the 1960s. Documentation is here understood as both the creation of documents and the techniques of their management, such as collection, archiving, arrangement, contextualization, or manipulation. The texts included here attend to the political, material, intermedial, and affective dimensions of documentation through close studies of specific artists and bodies of work. The authors consider a range of practices in experimental photography, conceptualism, and performance art, by artists situated in different local or transnational contexts—mostly Europe, North America, and East Asia. At stake are why and how the processes of making or organizing documents newly constituted an artistic practice in its own right during the 1960s. Building on established research on twentieth-century documentary strategies and key 1960s documents, as well as recent scholarship in media studies and performance studies, the issue fosters a richer understanding of the personal, political, and social uses of documentation in the period.